Influence of Quercus ilex trees on herbaceous production and nutrient concentrations in southern Portugal - Cubera, Elena; Manuel Nunes, Jorge; Madeira, Manuel; Gazarini, Luíz (Journal of Plant Nutrition and Soil Science, 2009)
In an open woodland in Portugal, the nature of interactions between Quercus ilex trees and herbaceous plants was assessed during 2 years by studying how manipulation of incident solar radiation, water and nutrient supply affect the herbaceous biomass and N, K, P, Ca, Mg, and Mn concentrations. Measurements were carried out in three environments consisting of (1) open grassland, (2) beneath the tree canopy, and (3) under artificial shade. Each of these environments was subjected to two regimes of fertilization and two water levels in a factorial design. The fertilizer treatment consisted of application of no fertilizer or a combination of 200 kg calcium ammonium nitrate ha–1 (26% N) and 350 kg superphosphate ha–1 (8% P), while the water-supply treatment consisted of either no irrigation or irrigation fortnightly from February 1 to April 30. Grasses showed significantly lower nutrient concentrations than forbs. However, nutrient concentrations of the whole herbaceous community were within the recommended ranges for cattle nutrition. A negative effect of shade on herbaceous biomass production was observed. The effect of watering on herbaceous biomass was less prominent than the effect of fertilization, irrespective of the environment, suggesting that Q. ilex does not compete for soil-water resources with herbaceous biomass in this ecosystem. Fertilization increased total biomass by 106%, 49%, and 97% in the open grassland, beneath the tree canopy, and under artificial shade, respectively. During the first and second year, fertilization increased herbaceous P concentrations by 24% and 83%, respectively, if compared with concentrations obtained at the unfertilized plots. Higher K and Mg concentrations were observed in herbaceous plants beneath the tree canopy than in the open areas, indicating a positive effect of trees on pasture quality. The positive and negative effects of trees on understory forage are discussed.
Keywords: fertilization; herbaceous biomass; irrigation; shade

Influence of Quercus ilex trees on herbaceous production and nutrient concentrations in southern Portugal - Cubera, Elena; Manuel Nunes, Jorge; Madeira, Manuel; Gazarini, Luíz (Journal of Plant Nutrition and Soil Science, 2009)
In an open woodland in Portugal, the nature of interactions between Quercus ilex trees and herbaceous plants was assessed during 2 years by studying how manipulation of incident solar radiation, water and nutrient supply affect the herbaceous biomass and N, K, P, Ca, Mg, and Mn concentrations. Measurements were carried out in three environments consisting of (1) open grassland, (2) beneath the tree canopy, and (3) under artificial shade. Each of these environments was subjected to two regimes of fertilization and two water levels in a factorial design. The fertilizer treatment consisted of application of no fertilizer or a combination of 200 kg calcium ammonium nitrate ha–1 (26% N) and 350 kg superphosphate ha–1 (8% P), while the water-supply treatment consisted of either no irrigation or irrigation fortnightly from February 1 to April 30. Grasses showed significantly lower nutrient concentrations than forbs. However, nutrient concentrations of the whole herbaceous community were within the recommended ranges for cattle nutrition. A negative effect of shade on herbaceous biomass production was observed. The effect of watering on herbaceous biomass was less prominent than the effect of fertilization, irrespective of the environment, suggesting that Q. ilex does not compete for soil-water resources with herbaceous biomass in this ecosystem. Fertilization increased total biomass by 106%, 49%, and 97% in the open grassland, beneath the tree canopy, and under artificial shade, respectively. During the first and second year, fertilization increased herbaceous P concentrations by 24% and 83%, respectively, if compared with concentrations obtained at the unfertilized plots. Higher K and Mg concentrations were observed in herbaceous plants beneath the tree canopy than in the open areas, indicating a positive effect of trees on pasture quality. The positive and negative effects of trees on understory forage are discussed.
Keywords: fertilization; herbaceous biomass; irrigation; shade

Elevated atmospheric CO2 does not modify osmotic adjustment to light and drought in the Mediterranean oak" Quercus suber L." - Aranda, I; Simón, J Puértolas (Investigación agraria. Sistemas y recursos forestales, 2008)
The current ongoing increase in the atmospheric CO2 concentration is an unquestionable fact. Thus, plants are bound to live in a more enriched CO2 world in a not far-off future. In this new framework, regeneration of forest tree species may be modified as a consequence of the change in the current patterns of seedling response to other environmental resources, such as water or light. We studied the impact of an elevated CO2 concentration on the interaction of drought and light upon the water relations of cork oak (Quercus suber L.) seedlings. In a complete factorial design of contrasting light (HL vs LL), water (WW vs S) and CO2 levels (800 ppm vs 370 ppm), we analysed the influence of each factor and its interaction in the modification of different leaf water parameters in potted seedlings after a 6 months experimental period. These parameters were derived from the construction, with leaf materials, of the P-V curves: osmotic potential at full turgor (Ψπ100), osmotic potential at zero turgor (Ψπ0), modulus of elasticity at full turgor (εmax), and the ratio dry/turgor weight (DW/TW). Doubling of the CO2 levels over the current concentration (380 ppm) did not change any of the studied leaf water parameters, while light and water availabilities had a significant influence. This result does not exclude changes in other basic physiological parameters that could modify the pattern of cork oak regeneration responding to a CO2 enriched atmosphere in the future, and under climatic conditions different to the current ones
Keywords: CO2 enrichment; Cork oak; PV curves; shade; Water availability

Elevated atmospheric CO2 does not modify osmotic adjustment to light and drought in the Mediterranean oak" Quercus suber L." - Aranda, I.; Simón, J. Puértolas (Investigación agraria. Sistemas y recursos forestales, 2008)
The current ongoing increase in the atmospheric CO2 concentration is an unquestionable fact. Thus, plants are bound to live in a more enriched CO2 world in a not far-off future. In this new framework, regeneration of forest tree species may be modified as a consequence of the change in the current patterns of seedling response to other environmental resources, such as water or light. We studied the impact of an elevated CO2 concentration on the interaction of drought and light upon the water relations of cork oak (Quercus suber L.) seedlings. In a complete factorial design of contrasting light (HL vs LL), water (WW vs S) and CO2 levels (800 ppm vs 370 ppm), we analysed the influence of each factor and its interaction in the modification of different leaf water parameters in potted seedlings after a 6 months experimental period. These parameters were derived from the construction, with leaf materials, of the P-V curves: osmotic potential at full turgor (Ψπ100), osmotic potential at zero turgor (Ψπ0), modulus of elasticity at full turgor (εmax), and the ratio dry/turgor weight (DW/TW). Doubling of the CO2 levels over the current concentration (380 ppm) did not change any of the studied leaf water parameters, while light and water availabilities had a significant influence. This result does not exclude changes in other basic physiological parameters that could modify the pattern of cork oak regeneration responding to a CO2 enriched atmosphere in the future, and under climatic conditions different to the current ones
Keywords: CO2 enrichment; Cork oak; PV curves; shade; Water availability

Canopy vs. soil effects of shrubs facilitating tree seedlings in Mediterranean montane ecosystems - Gómez-Aparicio, LORENA; Gómez, Jose M.; Zamora, Regino; Boettinger, Janis L. (Journal of Vegetation Science, 2005)
Abstract. Question: Is the facilitative effect of nurse shrubs on early recruitment of trees mediated by a ‘canopy effect’(microclimate amelioration and protection from herbivores), a ‘soil effect’(modification of soil properties), or both? Location: Two successional montane shrublands at the Sierra Nevada Protected Area, SE Spain. Method: Seedlings of Quercus and Pinus species were planted in four experimental treatments: (1) under shrubs; (2) in open interspaces without vegetation; (3) under shrubs where the canopies were removed; (4) in open interspaces but covering seedlings with branches, mimicking a shrub canopy. Results: Both effects benefited seedling performance. However, microclimatic amelioration due to canopy shading had the strongest effect, which was particularly pronounced in the drier site. Below-ground, shrubs did not modify soil physical characteristics, organic matter, total N and P, or water content, but significantly increased available K, which has been shown to improve seedling water-use efficiency under drought conditions. Conclusions: We propose that in Mediterranean montane ecosystems, characterised by a severe summer drought, pioneer shrubs represent a major safe site for tree early recruitment during secondary succession, improving seedling survival during summer by the modification of both the above-and below-ground environment.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: Nurse shrub; Positive interaction; Potassium; Removal experiment; shade

Growth and survival in Quercus ilex L. seedlings after irrigation and artificial shading on Mediterranean set-aside agricultural land - Rey Benayas, José M. (Ann. For. Sci., 1998)
Considerable quantities of agricultural land are being transformed into forested lands in E.U. countries. To assess afforestation practice, we analyzed the growth and survival of 800 Quercus ilex sp. ballota seedlings in set-aside agricultural land under semi-arid Mediterranean climate conditions in central Spain. The survival and growth of the seedlings were monitored for 3 years after planting with an experimental design that included all four combinations of: i) irrigation or no irrigation during the dry season; and ii) artificial shading or no shading. Significant differences in survival and growth (height, stem diameter and crown projected area) were found among treatments. Survival was lowest (53 %) in the control plots, and very similar (around 93 %) for the irrigation, shade and combined treatments. Most of the mortality occurred after the first dry season. The high survival rate in irrigated but not shaded plots coincided with a thick layer of the weed Amaranthus retroflexus L. (in the first dry season). Seedling growth was greatest on average under irrigation and shade conditions. Shade was found to have a significant effect for all growth measurements, while irrigation alone only affected stem diameter growth and crown projected area in interaction with shade. Growth measurements were correlated to microclimatic conditions in the plots as measured by the amounts of water and actual evapotranspiration. We conclude that the attenuation of summer stress must be considered in the early stages of successful plantation practice of set-aside agricultural land in a dry environment.
Keywords: Agricultural land; Growth; irrigation; shade; Survival

Growth and survival in Quercus ilex L. seedlings after irrigation and artificial shading on Mediterranean set-aside agricultural land - Rey Benayas, José M (Ann. For. Sci., 1998)
Considerable quantities of agricultural land are being transformed into forested lands in E.U. countries. To assess afforestation practice, we analyzed the growth and survival of 800 Quercus ilex sp. ballota seedlings in set-aside agricultural land under semi-arid Mediterranean climate conditions in central Spain. The survival and growth of the seedlings were monitored for 3 years after planting with an experimental design that included all four combinations of: i) irrigation or no irrigation during the dry season; and ii) artificial shading or no shading. Significant differences in survival and growth (height, stem diameter and crown projected area) were found among treatments. Survival was lowest (53 %) in the control plots, and very similar (around 93 %) for the irrigation, shade and combined treatments. Most of the mortality occurred after the first dry season. The high survival rate in irrigated but not shaded plots coincided with a thick layer of the weed Amaranthus retroflexus L. (in the first dry season). Seedling growth was greatest on average under irrigation and shade conditions. Shade was found to have a significant effect for all growth measurements, while irrigation alone only affected stem diameter growth and crown projected area in interaction with shade. Growth measurements were correlated to microclimatic conditions in the plots as measured by the amounts of water and actual evapotranspiration. We conclude that the attenuation of summer stress must be considered in the early stages of successful plantation practice of set-aside agricultural land in a dry environment.
Keywords: Agricultural land; Growth; irrigation; shade; Survival

Mortalidad y crecimiento de plantones de quercus ilex en una tierra agrícola abandonada en toledo - Rey Benayas, Jose Maria (II Congreso Forestal Español, 1997)
Considerable quantities of agricultural land are being transformed into forested lands in E.U. countries. To assess afforestation practice, we analyzed the growth and mortality of 800 Quercus ilex' subsp. ball()ta seedlings in a set-aside agricultural land under semi-arid Mediterranean climate conditions in Toledo, Spain. The mortality and growth of the seedlings were monitored for three years after planting with an experimental design that included all four combinations of i) irrigation or no irrigation in the dry season and ii) artificial shading or no shading. Significant differences in mortality and growth (height, stem diameter and crown projected area) were found among treatments. Mortality was highest (47%) in the control plots, and very similar (around 7%) for the irrigation, shade, and combined treatments. Most of the mortality occurred after the first dry season. The low mortality in irrigated but not shaded plots in the first dry season is attributed to the protective role of a thick layer of the weed Amaranthus retroflexus L. Seedling growth was greatest on average under irrigation and shade conditions. Shade was found to have a significant effect for all growth measurements, while irrigation alone only affected stem diameter growth, and crown projected area in interaction with shade. We conclude that the reduction of summer stress must be considered in the early stages for successfull afforestation practices with oaks in set-aside agricultural lands of dry environments.
Keywords: Agriculturalland; Growth; irrigation; shade; Survival